The correlation between agility and performance among blind and visually impaired athletes - Nagoor Meera Abdullah; Vincent Parnabas; Mohd Soffian Omar-Fauzee; Muhamad Nizam Nazaruddin (2014)
Regular physical activity has benefits on physical fitness among visually impaired athletes. The purpose of this study is to investigate how the motor fitness of agility influences the performance of the athletes. Total of 39 athletes (24 males and 15 females) were recruited for this study and were differentiate between their medical classes (totally blind athletes (B1) – male (n=10); females (n=8) and partially blind athletes (B2)- males (n=14); females (n=7). Subject?s height and weight was measured to determine the BMI level. Subjects was also required to undergo the lateral change of direction test was used to determine the agility among the athletes. Each of the subjects was required to complete 2 trials and the average score was recorded. The entire tests were analyzed using SPSS and presented as mean. Independent T-Test showed that there are significant differences in agility levels between b1 and B2 athletes. Correlation was also significant (p < 0.01; r = –.581) between classification groups and tests time scores. B1 and B2 athlete?s agility levels were slightly difference which also will affect their performance. Based on this data, future studies were suggested on non-athletes population.